CHELYABINSK METEOROID ACOUSTIC EFFECTS - Chernogor, L. F. (Видавничий дім «Академперіодика», 2017)
PACS numbers: 94.20.-y,96.30.Ys Purpose: The parameters (period, time delay, celerity, duration, and the rate of attenuation) of the acoustic signal which was generated during the Chelyabinsk meteoroid passage and explosion on February 15, 2013 are investigated along with atmospheric parameters.Design/methodology/approach: With the temporal variations in the level of the acoustic signals acquired at an array of acoustic stations, the principal signal parameters are determined and their comparison made with the model results.Findings: The time delay of the infrasound signal has been shown to increase approximately linearly with the distance between the acoustic source and an observation station. The mean celerity of the infrasound wave is approximately 270 m/s. The signal spectrum exhibits components with periods of 10÷100 s, and the harmonic with an approximately 30-s period prevails. The duration of the infrasound signal is established by its source length (50÷90 km) and the infrasound signal spreading due to dispersion in the atmosphere that depends on the distance the wave has traveled. The overall duration of the signal is equal to 6÷30 min for the range of 540÷ 5780 km. The regression relations between the time delays and the acoustic signal spreading have been determined as a function of path length. The characteristic scale length of infrasound attenuation depends on a specific path and varies within 1000÷3000 km. The effect of the moving shock created by the explosion is shown to be much greater than the effect of the ballistic wave almost at all altitudes.Conclusions: The estimates substantially agree with the observations.Key words: meteoroid kinetic energy, acoustic efficiency, mean wind speed, acoustic signal duration and time delay, moving shock parameters, oscillation periodManuscript submitted: 13.12.2016Radio phys. radio astron. 2017, 22(1): 53-66REFERENCES1. ALEKSEEV, V. A., ed. 2013.  Proceedings of the international scientific-practical conference "Asteroids and comets. Chelyabinsk event and study of the meteorite falling into the lake Chebarkul". Chelyabinsk, Russia: KraiRa Publ. (in Russian). 2. ALPATOV, V. V., BUROV, V. N., VAGIN, J. P., GALKIN,K. A., GIVISHVILI, G. V., GLUHOV, J. V., DAVIDENKO, D. V., ZUBACHEV, D. S., IVANOV, V. N., KARHOV, A. N., KOLOMIN, M. V., KORSHUNOV, V. A., LAPSHIN, V. B., LESHENKO, L. N., LYSENKO, D. A., MINLIGAREEV, V. T., MOROZOVA, M. A., PERMINOVA, E. S., PORTNYAGIN, J. I., RUSAKOV, J. S., STAL, N. L., SYROESHKIN, A. V., TERTYSHNIKOV, A. V., TULINOV, G. F., CHICHAEVA, M. A., CHUDNOVSKY, V. S. and SHTYRKOV, A. Y., 2013. Geophysical conditions at the explosion of the Chelyabinsk (Chebarkulsky) meteoroid in February 15, 2013. Moscow, Russia: FGBU "IPG" Publ. (in Russian). 3. GRIGORYAN, S. S., IBODOV, F. S. and IBADOV, S. I., 2013. Physical mechanism of Chelyabinsk superbolide explosion. Sol. Syst. Res. vol. 47, no. 4, pp. 268–274. DOI: https://doi.org/10.1134/S0038094613040151 4. SOLAR SYSTEM RESEARCH. 2013. vol. 47, no. 4. (Thematical issue). 5. ANTIPIN, N. A., ed. 2014. The Chelyabinsk Meteorite – one year on the Earth: Proceedings of All-Russian Scientific Conference. Chelyabinsk, Russia: Kamennyi poyas Publ. (in Russian). 6. EMEL'YANENKO, V. V., POPOVA, O. P., CHUGAI, N. N., SHELYAKOV, M. A., PAKHOMOV, YU. V., SHUSTOV, B. M., SHUVALOV, V. V., BIRYUKOV, E. E., RYBNOV, YU. S.,  MAROV,  M. YA., RYKHLOVA, L. V., NAROENKOV, S. A., KARTASHOVA, A. P., KHARLAMOV, V. A. and TRUBETSKAYA, I. A., 2013. Astronomical and Physical Aspects of Chelyabinsk Event (February 15, 2013). Sol. Syst. Res. vol. 47, is. 4, pp. 240–254. DOI: https://doi.org/10.1134/S0038094613040114 7. POPOVA, O. P., SHUVALOV, V. V., RYBNOV, Y. S., HARLAMOV, V. A., GLAZACHEV,  D. O., EMELIANENKO, V. V., KARTASHOVA, A. P. and JENNISKENS,  P., 2013. Chelyabinsk meteoroid parameters: Data analysis. In: Dinamicheskie protsessy v geosferah: sb. nauch. tr. IDG RAN. Moscow, Russia: Geos Publ. is. 4, pp. 10–21 (in Russian). 8. POPOVA, O. P., JENNISKENS, P., EMELYANENKO, V., KARTASHOVA, A., BIRYUKOV, E., KHAIBRAKHMANOV, S., SHUVALOV,  V., RYBNOV, Y., DUDOROV, A., GROKHOVSKY, V. I., BADYUKOV,  D. D., YIN, Q.-Z., GURAL, P. S., ALBERS, J., GRANVIK,  M., EVERS, L. G., KUIPER, J., HARLAMOV, V., SOLOVYOV, A., RUSAKOV, Y. S., KOROTKIY, S., SERDYUK, I., KOROCHANTSEV, A. V., LARIONOV,  M. Y., GLAZACHEV,  D.,  MAYER, A. E., GISLER, G., GLADKOVSKY, S. V., WIMPENNY, J., SANBORN, M. E., YAMAKAWA, A., VEROSUB, K. L., ROWLAND, D. J., ROESKE, S., BOTTO, N. W., FRIEDRICH, J. M., ZOLENSKY, M. E.,  LE, L., ROSS, D., ZIEGLER, K., NAKAMURA, T., AHN, I., LEE, J. I., ZHOU, Q., LI, X. H., LI, Q. L., LIU, Y., TANG, G.-Q., HIROI, T., SEARS, D., WEINSTEIN, I. A., VOKHMINTSEV, A. S., ISHCHENKO, A. V., SCHMITT-KOPPLIN, P., HERTKORN, N., NAGAO, K., HABA, M. K., KOMATSU, M. and MIKOUCHI, T., 2013. Chelyabinsk airburst, damage assessment, meteorite,   recovery and characterization. Science. vol. 342, is. 6162, pp. 1069–1073. DOI: https://doi.org/10.1126/science.1242642 9. POPOVA, O. P., JENNISKENS, P., EMELYANENKO, V., KARTASHOVA, A., BIRYUKOV, E., KHAIBRAKHMANOV, S., SHUVALOV, V., RYBNOV, Y.,  DUDOROV, A., GROKHOVSKY, V. I., BADYUKOV,  D. D., YIN, Q.-Z., GURAL, P. S., ALBERS, J., GRANVIK, M., EVERS, L. G., KUIPER, J., HARLAMOV, V., SOLOVYOV, A., RUSAKOV, Y. S., KOROTKIY, S., SERDYUK, I., KOROCHANTSEV, A. V., LARIONOV,  M. Y., GLAZACHEV,  D.,  MAYER, A. E., GISLER, G., GLADKOVSKY, S. V., WIMPENNY, J., SANBORN, M. E., YAMAKAWA, A., VEROSUB, K. L., ROWLAND, D. J., ROESKE, S., BOTTO,  N. W.,  FRIEDRICH,  J. M., ZOLENSKY, M. E, LE, L., ROSS, D., ZIEGLER, K., NAKAMURA, T., AHN, I., LEE, J. I., ZHOU, Q., LI, X. H., LI, Q. L., LIU, Y., TANG, G.-Q., HIROI, T., SEARS, D., WEINSTEIN, I. A., VOKHMINTSEV, A. S., ISHCHENKO, A. V., SCHMITT-KOPPLIN, P., HERTKORN, N., NAGAO, K., HABA, M. K., KOMATSU, M. and MIKOUCHI, T., 2013. Supplementary materials for Chelyabinsk airburst, damage assessment, meteorite,   recovery and characterization. Science [online]. vol. 342. [viewed 30 January 2017]. Available from: www.sciencemag.org/cgi/content/full/science.1242642/DC1 10. CHERNOGOR, L. F. and ROZUMENKO, V. T., 2013. The physical effects associated with Chelyabinsk meteorite's passage. Probl.  Atom. Sci. Tech. vol. 86, no. 4, pp. 136–139. 11. CHERNOGOR, L. F., 2013. The main physical effects associated with the Chelyabinsk bolide passage. In: Asteroids and comets. Chelyabinsk event and study of the meteorite falling into the lake Chebarkul: Proceedings of the international scientific-practical conference. Chelyabinsk, Russia: Krai Ra Publ., pp. 148–152 (in Russian). 12. CHERNOGOR, L. F., 2013. Plasma, electromagnetic and acoustic effects of meteorite Chelyabinsk. Inzhenernaya fizika. no. 8, pp. 23–40 (in Russian). 13. CHERNOGOR, L. F. and GARMASH, K. P., 2013. Disturbances in Geospace Associated with the Chelyabinsk Meteorite Passage. Radio Phys. Radio Astron. vol. 18, no. 3, pp. 231–243 (in Russian). 14. CHERNOGOR, L. F., 2013. Large-scale disturbances in the Earth's magnetic field associated with the Chelyabinsk meteorite. Radiofizika i elektronika. vol. 4 (18), no. 3, pp. 47–54 (in Russian). 15. CHERNOGOR, L. F., MILOVANOV, YU. B., FEDORENKO, V. N. and TSYMBAL, A. M., 2013. Satellite observations of the ionospheric disturbances followed by the fall of Chelyabinsk meteorite. Kosmіchna nauka і tekhnologіya. vol. 19, no. 6, pp. 38–46 (in Russian). 16. CHERNOGOR, L. F. and BARABASH, V. V., 2014. Ionosphere disturbances accompanying the flight of the Chelyabinsk body. Kinemat. Phys. Celest. Bodies. vol. 30, no. 3, pp. 126–136. DOI: https://doi.org/10.3103/S0884591314030039 17. CHERNOGOR, L. F., 2014. Geomagnetic field effects of the Chelyabinsk meteoroid. Geomagn. Aeron. vol. 54, no. 5, pp. 613–624. DOI: https://doi.org/10.1134/S001679321405003X 18. CHERNOGOR, L. F., 2015. Ionospheric effects of Chelyabinsk meteoroid. Geomagn. Aeron. vol. 55, no. 3, pp. 353–368.  DOI: https://doi.org/10.1134/S0016793215030044 19. RYBNOV, Y. S., POPOVA, O. P., HARLAMOV, V. A, SOLOVIEV, A. V., RUSAKOV, Y. S., GLUKHOV, A. G., SILBER, E., PODOBNAYA, E. D. and SURKOVA, D. V., 2013. Energy estimation of Chelyabinsk bolide using infrasound measurements. In: Dinamicheskie protsessy v geosferah: Sb. nauch. tr. IDG RAN. Moscow, Russia: Geos Publ. is. 4, pp. 21–32 (in Russian). 20. GOKHBERG, M. B., OL'SHANSKAYA, E. V., STEBLOV, G. M. and SHALIMOV, S. L., 2014. The Chelyabinsk meteorite: Ionospheric response based on GPS measurements. Doklady Earth Sciences. vol. 452, is. 1, pp. 948–952. DOI: https://doi.org/10.1134/S1028334X13090109 21. SOROKIN, A. G., 2014. On infrasonic radiation of Chelyabinsk meteoroid. In: V. I.  KURKIN, ed. Radio Waves Propagation: Proceedings of 24th All-Russian Scientific Conference. Irkutsk, Russia, 29 Jun – 5 Jul 2014. pp. 242–245(in Russian). 22. CHERNOGOR, L. F., 2014. Main effects of Chelyabinsk meteorite falling: physics and mathematics calculation results. In: ANTIPIN, N. A., ed. The Chelyabinsk Meteorite – one year on the Earth: Proceedings of All-RussianScientific Conference. Chelyabinsk, Russia: Kamennyi poyas Publ., pp. 229–264 (in Russian). 23. CHERNOGOR, L. F., 2013. Physical effects caused by flight of Chelyabinsk meteoroid. Dopovіdі Natsіonalnoi akademіi nauk Ukrainy. no. 10, pp. 97–104 (in Russian). 24. CHERNOGOR, L. F., 2015. Acoustic effects of Chelyabinsk meteoroid. In: 15th Ukrainian conference on space research Abstracts. 24–28 Aug. 2015, Odesa, Ukraine. p. 149. 25. REED, J., 1972. Airblast overpressure decay at long ranges. J. Geophys. Res. vol. 77, pp. 1623–1629. DOI: https://doi.org/10.1029/JC077i009p01623 26. REVELLE, D. O., 1976. On meteor-generated infrasound. J. Geophys. Res. vol. 81, pp. 1217–1231. DOI: https://doi.org/10.1029/JA081i007p01217 27. EDWARDS, W. N., BROWN, P. G. and REVELLE, D. O., 2006. Estimates of meteoroid kinetic energies from observations of infrasonic airwaves. J. Atmos. Sol.-Terr. Phys. vol. 68, is. 10, pp. 1136–1160. DOI: https://doi.org/10.1016/j.jastp.2006.02.010 28. STEVENS, J. L., ADAMS, D. A., BAKER, G. E., XU, H., MURPHY, J. R., DIVNOV, I., BOURCHIK, V. N. and KITOV,  I., 1999. Infrasound scaling and attenuation relations from Soviet explosion data and instrument design criteria from experiments and simulations. In: 21th Annual Seismic Research Symposium on monitoring a CTBT Proceedings. Las Vegas, Nevada. pp. 185–194. 29. SILBER, E. A., REVELLE, D. O., BROWN, P. G. and EDWARDS, W. N., 2009. An estimate of the terrestrial influx of  large meteoroids from infrasonic measurements. J. Geophys. Res. vol. 114, is. E8, id. E08006. DOI: https://doi.org/10.1029/2009JE003334 30. EDWARDS, W. N., 2010. Meteor Generated Infrasound:Theory and Observation. In: A. LE PICHON, E. BLANC, A. HAUCHECORNE, eds. Infrasound Monitoring for Atmospheric Studies. Dordrecht, Heidelberg, London, NewYork: Springer, pp. 361–414. 31. SILBER, E. A., LE PICHON, A. and BROWN, P. G., 2011. Infrasound detection of a near-Earth object impact over Indonesia on 8 October 2009. Geophys. Res. Lett. vol. 38, is. 12, id L12201. DOI: https://doi.org/10.1029/2011GL047633 32. ENS, T. A., BROWN, P. G., EDWARDS, W. N. and SILBER, E. A., 2012. Infrasound production by bolides:A global statistical study. J. Atmos. Solar-Terr. Phys. vol. 80, pp. 208–229. DOI: https://doi.org/10.1016/j.jastp.2012.01.018 33. LE PICHON, A., CERANNA, L., PILGER, C., MIALLE,P., BROWN, D., HERRY, P. and BRACHET, N., 2013. The 2013 Russian fireball largest ever detected by CTBTO infrasound sensors. Geophys. Res. Lett. vol. 40, is. 14, pp. 3732–3737. DOI: https://doi.org/10.1002/grl.50619 34. CHERNOGOR, L. F., 2012. Physics and ecology of the catastrophes. Kharkiv: V. N. Karazin Kharkiv National University Publ. (in Russian). 35. CHERNOGOR, L. F., 2011. Oscillations of the geomagnetic field caused by the flight of Vitim bolide on September 24, 2002. Geomagn. Aeron. vol. 51, no. 1, pp. 116–130. DOI: https://doi.org/10.1134/S0016793211010038 36. BROWN, P., HILDEBRAND, A. R., GREEN, D. W. E., PAGÉ, D., JACOBS, C., REVELLE, D., TAGLIAFERRI, E., WACKER, J. and WETMILLER, B., 1996. The Fall of the St-Robert. Meteorit. Planet. Sci. vol. 31, is. 4, pp. 502–517. DOI: https://doi.org/10.1111/j.1945-5100.1996.tb02092.x 37. BROWN, P., REVELLE, D. O., TAGLIAFERRI, E. and HILDEBRAND, A. R., 2002. An Entry Model for the Tagish Lake Fireball Using Seismic, Satellite and Infrasound Records. Meteorit. Planet. Sci. vol. 37, is. 5, pp. 661–675. DOI: https://doi.org/10.1111/j.1945-5100.2002.tb00846.x 38. BROWN, P. G., WHITAKER, R. W., REVELLE, D. O. and TAGLIAFERRI, E. 2002. Multi-station Infrasonic Observations of Two Large Bolides: Signal Interpretation and Implications for Monitoring of Atmospheric Explosions. Geophys. Res. Lett. vol. 29, is. 13, pp. 14-1–14-4. DOI: https://doi.org/10.1029/2001GL013778 39. BOROVIČKA, J., WEBER, H. W., JOPEK, T., JACES, P., RANDA, Z., BROWN, P. G., REVELLE, D. O., KALENDA, P., SCHULTZ, L., KUČERA, J., HALODA, J., TYCOVÁ, P.,  FRYDA, J. and BRANDSTÄTTER, F., 2003. The Morávka Meteorite Fall: 3. Meteoroid Initial Size, History, Structure and Composition. Meteorit. Planet. Sci. vol. 38, is. 7, pp. 1005–1021. DOI: https://doi.org/10.1111/j.1945-5100.2003.tb00295.x 40. PASECHNIK, I. P., 1962. Science has proved that nuclear explosions can be detected any place. Priroda. no. 7, pp. 3–12 (in Russian).